Strictureplasty - Hesham, Walid; Kann, Brian R. (Clinics in Colon and Rectal Surgery, 2013)
Over the past three decades, strictureplasty for Crohn disease with fibrostenotic stricture has been shown to be both efficacious and safe. Although segmental resection remains the standard of care for obstruction secondary to Crohn stricture, strictureplasty should be considered for patients with a history of prior resections who are at increased risk for short bowel syndrome with additional resections. There is ample evidence to support both conventional and nonconventional strictureplasty techniques for both jejunoileal and ileocolonic anastomotic strictures. The role of strictureplasty for both duodenal and colonic disease, as well as the risk of malignant transformation at strictureplasty sites, is yet to be determined.
Keywords: strictureplasty; Crohn disease; stricture; obstruction